Bioactive extracellular matrix scaffolds engineered with proangiogenic proteoglycan mimetics and loaded with endothelial progenitor cells promote neovascularization and diabetic wound healing - Siqi He (KeAi Communications Co., Ltd., 2022)
Diabetic ischemic wound treatment remains a critical clinical challenge. Neovascularization plays a significant role in wound healing during all stages of the tissue repair process. Strategies that enhance angiogenesis and neovascularization and improve ischemic pathology may promote the healing of poor wounds, particularly diabetic wounds in highly ischemic conditions. We previously identified a cyclic peptide LXW7 that specifically binds to integrin αvβ3 on endothelial progenitor cells (EPCs) and endothelial cells (ECs), activates vascular endothelial growth factor (VEGF) receptors, and promotes EC growth and maturation. In this study, we designed and synthesized a multi-functional pro-angiogenic molecule by grafting LXW7 and collagen-binding peptides (SILY) to a dermatan sulfate (DS) glycosaminoglycan backbone, named LXW7-DS-SILY, and further employed this multi-functional molecule to functionalize collagen-based extracellular matrix (ECM) scaffolds. We confirmed that LXW7-DS-SILY modification significantly promoted EPC attachment and growth on the ECM scaffolds in vitro and supported EPC survival in vivo in the ischemic environment. When applied in an established Zucker Diabetic Fatty (ZDF) rat ischemic skin flap model, LXW7-DS-SILY-functionalized ECM scaffolds loaded with EPCs significantly improved wound healing, enhanced neovascularization and modulated collagen fibrillogenesis in the ischemic environment. Altogether, this study provides a promising novel treatment to accelerate diabetic ischemic wound healing, thereby reducing limb amputation and mortality of diabetic patients.